2008
DOI: 10.1007/s10551-008-9996-5
|View full text |Cite
|
Sign up to set email alerts
|

Guanxi and Business Ethics in Confucian Society Today: An Empirical Case Study in Taiwan

Abstract: auditor independence, Confucianism, corruption, culture, guanxi , social networks,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 21 publications
2
90
0
Order By: Relevance
“…It refers to the social ties that people develop and use for instrumental purposes (Gold, 1985;Jacobs, 1979Jacobs, , 1982Walder, 1986;Yang, 1994). Numerous studies have found that guanxi serves as one of the primary channels through which firms obtain resources and support (e.g., Au and Wong, 2000;Hwang et al, 2009). Guanxi can bring a wide range of benefits to businesses, such as securing rare resources, bypassing or short-cutting the bureaucratic maze, obtaining information and privilege, selling otherwise unsellable goods, and providing insurance against uncertainty and assistance when problems arise (Fan, 2002;Fock and Woo, 1998;Tsang, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It refers to the social ties that people develop and use for instrumental purposes (Gold, 1985;Jacobs, 1979Jacobs, , 1982Walder, 1986;Yang, 1994). Numerous studies have found that guanxi serves as one of the primary channels through which firms obtain resources and support (e.g., Au and Wong, 2000;Hwang et al, 2009). Guanxi can bring a wide range of benefits to businesses, such as securing rare resources, bypassing or short-cutting the bureaucratic maze, obtaining information and privilege, selling otherwise unsellable goods, and providing insurance against uncertainty and assistance when problems arise (Fan, 2002;Fock and Woo, 1998;Tsang, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery that guanxi has been abused in Taiwan prompts managers and employees operating in Confucian cultures to be wary when their Chinese colleagues and business partners are practising guanxi (Hwang, Goleman, Chen, Wang, & Hung, 2009). In addition, when faced with guanxi-related ethical dilemmas, Chinese employees at lower Kohlbergian stages of moral reasoning saw guanxi behaviour in a more positive light than those at higher stages (Ho & Redfern, 2010).…”
Section: Cultural Diversity and Moral Climatesmentioning
confidence: 99%
“…In such a case, gaunxi members react negatively to any deviance that disturbs the order, potentially destabilizes or erode it. Besides, failure by a gaunxi member to uphold the social rules and meeting gaunxi responsibilities will result in damaged prestige, loss of face, and subsequent loss of trust by other members of the gaunxi circle (Hwang, Golemon, Chen, Wang, and Hung, 2009). Thus, to save face gaunxi members abide by the social rules upon which gaunxi obligations and responsibilities are based (Wang, 2007).…”
Section: Social Rule System Theory and Gaunxi Rulesmentioning
confidence: 99%
“…Renqing, refers to one's emotional responses or a resource that one can present to another person as a gift in the social exchange process, and a set of social norms that one should follow to get along well with other people (Wang, 2007). If truth be told, what guides relational exchange behaviors in gaunxi distribution channels are the rules of reciprocal obligation and mutual assurance, which are also based on renqing (Hwang, Golemon, Chen, Wang, and Hung, 2009). In particular, gaunxi is cultivated and maintained through the exchange of renqing to attain mutual benefits.…”
Section: Social Rule System Theory and Gaunxi Rulesmentioning
confidence: 99%
See 1 more Smart Citation